Conversion of wheat husk to high surface area activated carbon for energy storage in high-performance supercapacitors. (January 2021) - Baig, Mutawara Mahmood; Gul, Iftikhar Hussain
Abstract: Conversion of carbon-containing biomass into useful carbon products is highly demanded. A rising understanding of environmental problems explains the growing focus on evaluating bioproducts and wastes in numerous applications. Herein, the wheat husks derived activated carbon (WHAC) was employed as electrode material for supercapacitors' energy storage. Three samples of activated carbon were made using wheat husks, which were activated at different temperatures. The prepared electrodes were characterized and electrochemically tested using Fourier-transform infrared spectroscopy, X-ray powder diffraction, scanning electron microscope, cyclic voltammetry, galvanostatic charge-discharge, and electrical impedance spectroscopy. The maximum capacitance (271.5 F g −1 at a current density of 0.5 A g −1 ) was observed for AC-800, activated at 800 °C. The electrochemical impedance showed low resistance (3.659 Ω) and low-frequency response (6.84 s). The AC-800 electrode exhibited the capacitance retention of 82% after 5000 cycles. The excellent electrochemical properties reveal the utilization of biomass waste as a potential electrode material for supercapacitors. The process used is simple, environmentally friendly, and could significantly reduce the county's biomass wastes from wheat husks. The approach can not only reduce environmental pollution but develop porous carbon electrodes for energy storage devices. Graphical abstract: Image 1 Highlights: The wheat husks derived activated carbon was prepared on Ni foam substrate. The activated carbon was chemically activated by impregnating KOH. The optimum activation temperature was found to be 800 °C. The electrode showed a high specific capacitance of 271.5 F/g. The electrode exhibited high energy, power density and cyclic stability.